Advances in the scaffolds fabrication techniques using biocompatible polymers and their biomedical application: A technical and statistical review - Adnan Haider; Sajjad Haider; Madhusudana Rao Kummara; Tahseen Kamal; Abdul-Aziz A Alghyamah; Faiza Jan Iftikhar; Bushra Bano; Naeem Khan; Mohammad Amjid Afridi; Sung Soo Han; Ali Alrahlah; Rawaiz Khan (Journal of Saudi Chemical Society)
With the advancement in tissue engineering, researchers are working hard on new techniques to fabricate more advanced scaffolds from biocompatible polymers with enhanced porosity, appropriate mechanical strength, diverse shapes and sizes for potential applications in biomedical field in general and tissue engineering in particular. These techniques include electrospinning, solution blow spinning, centrifugal spinning, particulate leaching (salt leaching), freeze-drying, lithography, self-assembly, phase separation, gas foaming, melt molding, 3-D printing, fiber mesh and solvent casting. In this article we have summarized the scaffold’s fabrication techniques from biocompatible polymers that are reported so far, the recent advances in these techniques, characterization of the physicochemical properties of scaffolds and their potential applications in the biomedical field and tissue engineering. The article will help both newcomers and experts working in the biomedical implant fabrication to not only find their desired information in one document but also understand the fabrication techniques and the parameters that control the success of biocompatible polymeric scaffolds. Furthermore, a static analysis of the work published in all forms on the most innovative techniques is also presented. The data is taken from Scopus, restricting the search to biomedical fields and tissue engineering. Keywords: Biocompatible polymeric Scaffolds, Scaffolds fabrication techniques, Tissue engineering, Biomedical application